Factors That Influence Reseller Purchasing Decisions - Gouwtama, Teddy; Tambunan, Damelina B. (KnE Social Sciences, 2021)
This study was conducted to examine what factors shape reseller purchasing decisions. This study used a quantitative approach by collecting data using questionnaires and then organizing the data using SPSS and SMART-PLS. The questionnaire was distributed to 68 respondents who were resellers from PT Dwitunggal Kencana Raya. This research used Confirmatory Factor Analysis (CFA). The factors used were derived from previous studies and were rational and emotional factors. Rational factors included product, brand image, price, distribution, promotion, service quality, information and warranty. Emotional factors included job assessment, incentives and interpersonal. The results of this study indicated that rational and emotional factors can be used to shape purchasing decisions at Jaguar Star resellers and for Dwitunggal management. Keywords: reseller, purchase decision, rational factors, emotional factors, CFA